T-bet and mucosal Th1 responses in the gastrointestinal tract. Issue 3 (1st September 2002) - Weigmann, B; Neurath, M F
Abstract : T cells play an essential role in regulating mucosal immune responses in the gastrointestinal tract. Recent observations on T helper cell differentiation and activation by regulatory transcription factors—especially T-bet—in chronic inflammatory diseases have provided new perspectives for understanding mucosal immunity. Here we summarise recent advances in the field of transcription factors and discuss the implications of these findings for future therapeutic approaches in inflammatory bowel diseases. In particular, we have focused on the role of T-bet in controlling mucosal Th1 responses in the gastrointestinal tract.